Changes in the Abundance of Danish Orchids over the Past 30 Years - Christian Damgaard; Jesper Erenskjold Moeslund; Peter Wind (Diversity, 2020)
Orchid abundance data collected over the past 30 years (1987–2016) from 440 sites within the National Orchid Monitoring Program were analyzed to quantify the population trends of orchids in Denmark, and the underlying reasons for the observed population trends were analyzed and discussed. Of the 45 monitored Danish orchids, 20 showed a significant decrease in abundance over the past 30 years (16, if only orchids with at least 50 observations each were selected), thus corroborating the previous observations of declining orchid abundances at the European scale. Generally, there was a significant negative effect of overgrowing with tall-growing herbs and shrubs on the abundance of Danish orchids, mainly caused by change of farming practices, as extensive management, such as grazing or mowing of light-open grassland areas, has decreased.